Anticipation and Medicine - Nadin, Mihai; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
In this book, practicing physicians and experts in anticipation present arguments for a new understanding of medicine. Their contributions make it clear that medicine is the decisive test for anticipation. The reader is presented with a provocative hypothesis: If medicine will align itself with the anticipatory condition of life, it can prompt the most important revolution in our time. To this end, all stakeholders-medical practitioners, patients, scientists, and technology developers-will have to engage in the conversation. The book makes the case for the transition from expensive, and only marginally effective, reactive treatment through "spare parts" (joint replacements, organ transplants) and reliance on pharmaceuticals (antibiotics, opiates) to anticipation-informed healthcare. Readers will understand why the current premise of treating various behavioral conditions (attention deficit disorder, hyperactivity, schizophrenia) through drugs has to be re-evaluated from the perspective of anticipation. In the manner practiced today, medicine generates dependence and long-lasting damage to those it is paid to help. As we better understand the nature of the living, the proactive view of healthcare, within which the science and art of healing fuse, becomes a social and political mandate.
Part I Anticipation and Medical Care -- Part II Evaluating the Risk Factors and Opportunities of New Medical Procedures -- Part III Examining the Brain -- Part IV Anticipation and Medical Data Processing -- Part V Anticipation and Psychological Aspects of Patient Treatments -- Part VI Anticipation and Ubiquitous Computing -- Part VII Anticipation and Alternative Medicine.
Keywords: Computational intelligence; Neural networks (Computer science) .; Artificial intelligence; Computational Intelligence; Mathematical Models of Cognitive Processes and Neural Networks; Artificial Intelligence